Epilepsy with myoclonic atonic seizures and chronic cerebellar symptoms associated with antibodies against glutamate receptors N2B and D2 in serum and cerebrospinal fluid. Issue 1 (March 2017) - Matsuura, Ryuki; Hamano, Shin‐ichiro; Ikemoto, Satoru; Hirata, Yuko; Suzuki, Kotoko; Kikuchi, Kenjiro; Takahashi, Yukitoshi
Abstract: A 3‐year‐old boy with normal development presented with acute cerebellitis at one year and 10 months of age. His truncal ataxia resolved without treatment. He experienced a relapse of truncal ataxia and atonic seizures at 2 years and one month of age. Five months later, he experienced myoclonic atonic seizures. By 3 years of age, the truncal ataxia had become severe, and the frequency of myoclonic atonic seizures increased. Compared to controls, we found higher levels of anti‐C‐terminal GluN2B and anti‐N terminal GluD2 antibodies in the serum, and anti‐N terminal GluN2B and anti‐C terminal GluD2 antibodies in the cerebrospinal fluid (CSF). A cell‐based assay revealed the presence of anti‐NMDA‐type glutamate receptor antibody in the serum, but absence in the CSF. Ictal EEG of myoclonic atonic seizures showed generalized spike and wave complexes. The patient was diagnosed with myoclonic atonic epilepsy. Adrenocorticotrophic hormone therapy resolved the truncal ataxia and myoclonic atonic seizures, along with the decreased serum anti‐C‐terminal GluN2B and anti‐N‐terminal GluD2 antibodies, and CSF anti‐N‐terminal GluN2B and anti‐C‐terminal anti‐GluD2 antibodies. Our results suggest that the anti‐GluN2B and anti‐GluD2 antibodies may be associated with myoclonic atonic epileptic seizures and chronic cerebellitis.